Virtual community consultation? Using the literature and weblogs to link community perspectives and health technology assessment - Street, Jackie M. (Health Expect, 2008)
Background  Community views, expressed in social impact assessments and collected through community consultation, should play an important role in health technology assessment (HTA). Yet HTA methodologists have been slow to include outcomes of these forms of inquiry in analyses, in part because collecting community views is time‐consuming and resource intensive. Objective  To explore how community views sourced from published studies, grey literature and informal internet web pages can inform HTA. Methods  A technology reviewed by Adelaide HTA in 2004 was selected: retinal photography for detection of diabetic retinopathy. Published literature, ‘grey’ literature and informal web pages were searched to examine the availability of evidence about service community and user community views with respect to this technology. Particular efforts were made to source evidence relating to rural, remote and Aboriginal populations. Results  We found that journal articles, reports from the grey literature and informal internet web pages (including blogs and discussion forums) can provide valuable insight into community views. Although there was little empirical evidence relating to the experience of diabetes and diabetes management in rural, remote and Aboriginal communities, there were indications that some evidence may be transferable from other populations. Conclusions  Community perspectives on selected health technologies can be gauged from available resources in published and grey literature and perspectives collected in this way can provide insight into whether the introduction of the technology would be acceptable to the community. The limitations of this approach are discussed.